PERFORMANCE EVALUATION OF MEDICINAL AND AROMATIC PLANTS IN HORTI-MEDICINAL AGROFORESTRY SYSTEM UNDER ARID REGIONS OF ANDHRA PRADESH - A , MALLISWARA REDDY (The Journal of Research ANGRAU, 2026)
A field experiment was conducted for evaluation of medicinal and aromatic plants in horti medicinal agroforestry system under semi-arid regions of Andhra Pradesh during kharif,2021 and 2022 at AICRPDA, Agricultural Research Station, Ananthapur. The treatments consist of four main plots (Trees) of size 72X 36 m viz., Simarouba, Custard apple, Jamun and Amla and three sub plots (Medicinal plants) of size 36 X 4 m viz., Aswagandha, Senna, Nannari and Velvet bean. The experiment was conducted in split plot design with three replications. During 2021, Amla trees, recorded an average fruit yield of 8.0 kg per tree and Jamun fruit yield was 8 kg per tree. During 2022, Amla trees recorded an average fruit yield of 9.3 kg per tree, jamun average fruit yield was 7.1 kg per tree and custard apple average fruit yield was 0.7 kg per tree. The present study findings showed that, in semi-arid regions of Andhra Pradesh, all of the tested medicinal plants performed better when grown as sole crops as compared to different tree-based intercropping systems. Sub plot treatments viz., medicinal plants intercropped in custard apple performed well (Mean leaf yield of Aswagandha was 1547 kg ha-1 , Aswagandha root dry weight was 87 kg ha-1 ; Senna leaf dry weight was 1674 kg ha-1 and velvet bean seed yield was 293 kg ha-1 )compared to other trees.